Parental low self-control, parental socialization, young adult low self-control, and offending: a retrospective study - Meldrum, Ryan Charles (Criminal justice and behavior, 2015)
Significant attention has been directed at evaluating Gottfredson and Hirschi?s claim that parental socialization has a direct influence on self-control and an indirect influence on criminal behavior. Yet, only recently have researchers investigated the role parental self-control occupies in shaping these processes. To advance research in this area, the current study utilizes data collected on a sample of young adults (n = 420) to examine how parental low self-control is related to parental socialization, young adult low self-control, and young adult offending. In support of the hypothesized model, the results of a structural equation model indicate the effect of parental low self-control on young adult low self-control is indirect through parental socialization, the effect of parental socialization on young adult offending is indirect through young adult low self-control, and the effect of parental low self-control on young adult offending is indirect through both parental socialization and young adult low self-control.